2019
DOI: 10.1108/jes-03-2019-0123
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fiscal transparency on government spending efficiency

Abstract: Purpose Making citizens able to monitor and evaluate public spending activities is a fundamental issue in public financial management literature. The purpose of this paper is to analyze whether fiscal transparency, measured by the Open Budget Index, has an effect on public spending performance, measured by the World Economic Forum’s Global Competitiveness Report data. Design/methodology/approach Research methods rely on random-effects panel regression models on a country-level panel data set of 82 world coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In addition, there are other unexpected factors that are difficult to predict (e.g. the 2020 coronavirus pandemic) (De Simone et al., 2019; Marek et al., 2020; Pierre and Peters, 2019).…”
Section: Results and Analysismentioning
confidence: 99%
“…In addition, there are other unexpected factors that are difficult to predict (e.g. the 2020 coronavirus pandemic) (De Simone et al., 2019; Marek et al., 2020; Pierre and Peters, 2019).…”
Section: Results and Analysismentioning
confidence: 99%
“…Chen and Neshkova (2020), we use the democracy index developed by the Economist Intelligence Unit, which is a composite indicator assessing the electoral process, civil liberties, the functioning of government, political participation, and political culture. The level of democracy affects politicians' incentives to change their behavior because lower democracy levels mean a lower probability of being sanctioned for misconduct, and hence lower accountability (De Simone et al, 2019). Moreover, the rule of law is an accountability mechanism that is believed to affect both politicians' and bureaucrats' incentives to engage in corrupt behavior, and citizens' willingness to use fiscal information and participate in budgetary stages (Chen & Ganapati, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a non-linear analysis helps to better represent the relationship between fiscal transparency and PSTE in the theoretical literature. Only two studies utilized cross-country data to empirically test the effect of fiscal transparency on PSTE, which are the studies by Montes et al (2019) andDe Simone et al (2019). The former study used a linear form of fiscal transparency and found that higher fiscal transparency has a positive linear effect on DEA PSTE scores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrying out exceptional government expenditures without releasing adequately open and accessible information about them implies a weaker system of checks and balances that reveals "system vulnerabilities" (Heald & Hodges, 2020) and exposes to the risk of corruptive practices (De Simone et al, 2017) or misuse of public funds (De Simone et al, 2019). Indeed, experts highlight that many of the government expenditures made during the Covid-19 crisis experienced this risk (International Budget Partnership, 2021).…”
Section: Introductionmentioning
confidence: 99%